Reestablishment of rural services and revitalization of rural economy - Goodland, Andrew (World Bank, Washington, DC, 2012)
This note presents relevant interventions that have aimed to stimulate rural economies a natural disaster based on case studies from the Philippines, Turkey, and Pakistan. Introducing new, untested infrastructure methods or designs involves careful analysis and may delay reconstruction. If this level of analysis is not completed, the reconstructed infrastructure may not meet expectations. For example, in Turkey, the Erzincan earthquake, new earthquake-resistant barns were built according to designs approved by the state. However, the insulation was insufficient for such an intemperate region so farmers abandoned the barns or used them for other purposes. In reconstruction work, relying on simple, well-tested, and easily scalable solutions may be more efficient if an appropriate level of analysis of innovation is not available. The priority for farmers and for other businesses is to reestablish their livelihoods as soon as possible. For farmers this means getting back to their land and/or livestock to maintain seasonally driven activities. This need to restart economic activities is often more urgent than the reconstruction of dwellings or other critical infrastructure.